Corvoheteromeyenia Ezcurra de Drago, 1979 (Spongillidae, Porifera): Genus review with proposal of neotype of Corvoheteromeyenia heterosclera (Ezcurra de Drago, 1974) - Calheira, Ludimila; Pinheiro, Ulisses (Zootaxa, 2016)
Corvoheteromeyenia Ezcurra de Drago, 1979 (Spongillidae) is endemic to the Neotropical Region and was erected to comprise C. australis (Bonetto & Ezcurra de Drago, 1966) and C. heterosclera (Ezcurra de Drago, 1974). However, the distinction between these species was not well-established and the type materials were not deposited in the collections as otherwise indicated in the original descriptions. Thus, in order to elucidate their specific status, this paper provides a review of the genus and proposes a neotype designation of Corvoheteromeyenia heterosclera, following Article 75 of the International Code for Zoological Nomenclature (ICZN 1999). A total of 41 specimens were analyzed and identified as belonging to Corvoheteromeyenia. Based on the literature and additional specimens, the redescription of C. australis and C. heterosclera is presented. The acanthoxea microscleres were stated as the distinctive character of both, but are present only in C. heterosclera. Corvoheteromeyenia sanidastosclera Pinheiro, Silva & Calheira, 2015, is distinct from congeners by the presence of sanidaster gemmuloscleres and also differ from C. heterosclera by the absence of acanthoxea microscleres. A key to species of Corvoheteromeyenia is provided.